(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
A decline in labour force and wage cuts are among the factors that determine macroeconomic trends. Since workers are normally motivated by significantly higher wages in other companies, these factors can reduce labour mobility. Moreover, we are witnessing trends related to the share of labour force, capital and output growth. This paper supports the thesis according to which these trends are rooted in the increase of the market power starting from the 1980s. Furthermore, this paper analyses the development of the margins using the company-level data in the USA economy from the1950s on. Initially, the margins were stable, or on a slight decline. Average margins had an increase of 18% above the marginal cost in the 1980s compared to the 67% growth that we are witnessing nowadays. There seems to be no clear pattern identifiable across the industries, but the margins tend to be higher in smaller companies in all industries and the higher growth is usually registered as a result of growth within an industry.